ANALISIS PENGARUH PERSEPSI RISIKO, KUALITAS SITUS WEB, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN E-COMMERCE SHOPEE DI KOTA SEMARANG - Zulfa, Latifah; Hidayati, Retno (Diponegoro Journal of Management, 2018)
This study was conducted to analyze the factors that affect consumers in the city of Semarang in making purchasing decisions on e-commerce shopee. The independent variables consist of perceived risk (X1), website quality (X2), and consumer trust (X3). The dependent variable is the purchase decision (Y).In this study the sample amounted to 100 respondents taken using accidental sampling technique. The questionnaire test was done by semantic test analysis technique and statistical test. Data processing is done by index number and multiple linear regression analysis by fulfilling the classical assumption, R2 test and F test and t test.Â The result of multiple linear regression equation is, Y = -0.127 X1 + 0,288 X2 + 0,367 X3. The independent variable that has the most influence on the dependent variable is variable consumer trust (0.367). R2 test results show that the independent variables can only explain by 43% dependent variable. F test results state that the model offered is feasible or fit. The result of t test shows that perceived risk has negative effect and not significant on purchasing decision, while website quality and consumer trust have positive effect and significant to purchasing decision.